Does the Transition to Grandparenthood Deter Gray Divorce? A Test of the Braking Hypothesis. (30th April 2020) - Brown, Susan L; Lin, I-Fen; Mellencamp, Kagan A
Abstract: The gray divorce rate, which describes divorce among individuals aged 50 and older, has doubled since 1990. Extending prior research that showed the transition to parenthood has a "braking effect" on divorce, we examined whether the transition to grandparenthood, an emotionally meaningful midlife event that typically renews midlife marriages, exerts an analogous "braking effect" on gray divorce. Using panel data from the 1998–2014 Health and Retirement Study, we found that becoming biological grandparents has a large deterrent effect on gray divorce that persists even after accounting for a host of other factors known to be associated with divorce. However, the transition to step grandparenthood has no protective effect on gray divorce. Our study demonstrates the importance of the larger family system and in particular the life webs connecting the generations for promoting marital stability among midlife couples.